(untitled) (Ameghiniana, 2025)
This paper reports the discovery of Late Jurassic scales of marine actinopterygian fishes from the basal portion of the Ameghino (= Nordenskjöld) Formation in Longing Gap, Antarctic Peninsula. Two new fish-bearing horizons are recognized, supplementing the three previously known. The identified scales are of two types: large rounded (= elasmoid) of amioid-type, and large rhomboid (= ganoid). The amioid-type scales are attributed to Amiiformes and classified into five distinct morphotypes; the rhomboid scales are assigned to indeterminate †Ginglymodi under two morphotypes. We briefly discuss the taphonomic processes that affected the preservation of the material. Furthermore, we discuss the role of marine pathways (i.e., the Hispanic and Mozambique corridors) that Amiiformes and †Ginglymodi might had used during the Late Jurassic from the Tethys Sea––where they originated––to the Larsen Basin in the Antarctic Peninsula. The evidence presented here represents the first record of Amiiformes in Antarctica and the southernmost records for both, Amiiformes and †Ginglymodi, worldwide.